Initial Investigation Into Real 3D Body Scanning Versus Avatars for the Virtual Fitting of Garments - Balach Monika (Autex Research Journal, 2020)
The clothing industry is currently focused on 3D virtual fitting. Many companies use size 12 as the core size; however, in recent years the average size has increased. For example, in the United Kingdom, the average size is now 16. Many companies have not updated their core size and often use size 12 as the size they are the most familiar with. The purpose of this paper is to compare real plus size body shapes with artificial avatars in relation to the fabric draping. This paper will investigate, how the body shape changes with an age (body height decreases, skin elasticity is lower, the shoulders are hunched, buttocks sag and fatness pockets are accumulated around the waist area). These factors are not considered in virtual avatars, but have a big impact on virtual fitting.